Entrepreneurs as change agents in remote communities: a multi-case study analysis in Newfoundland and Labrador, Canada. (21st July 2022) - Walsh, Jacqueline S.; Hall, Heather
Over the last decade, small communities and local economic development have become a focal point of research on entrepreneurship. The contributions of individuals have not gone unnoticed in the creation of economic opportunities through building entrepreneurial communities. Based on two case studies from remote communities in Newfoundland and Labrador, Canada, we find that successful entrepreneurs living in small communities can have a special dynamic in their communities and may be responsible for change in various ways and under a variety of contexts. Change may be economic, social, institutional, political, environmental and/or any other nature of transformation that is required to ensure the community in which they chose to live is sustainable and offers a viable standard of living for its residents. We argue that the distinction between social and business entrepreneurs is less pronounced in small communities in isolated regions and that solving social issues necessitates a focus on economic revitalisation.